Preliminary Functional Analysis of the Gut Microbiome in Colic Horses - Pamela Thomson; Daniel Garrido; Rodrigo Santibáñez; Felipe Lara (Animals, 2024)
The gut microbiome plays a critical role in maintaining horse health, influencing digestion, immunity, and overall well-being. However, in certain conditions like colic, there is evidence of significant alterations in the microbial community. To analyze the composition of the fecal microbiome and the enriched predicted metabolic functions of horses with colic compared to a control group, 14 horses with colic and 14 control horses were recruited. From a stool sample, DNA extraction was carried out for subsequent 16S rRNA metagenomic analysis. The composition of the microbiome was analyzed from the sequences of each sample using the QIIME version 1.8.0 and DADA2 version 1.22 programs. PICRUSt2 was used to predict metabolic functions. Statistical analyses were performed with the Mann–Whitney U test from the Python scipy v1 package. The gut microbiomes of both groups were dominated by Firmicuteota, Bacteroidota, and Pseudomonadota phyla. Colic in horses was associated with reduced diversity, reduced abundance of Fibrobacter, and an increase in Streptococcus. The abundance of Firmicuteota was negatively correlated with Pseudomonadota and Actinobacteriota. The equine colic microbiome was predicted to be enriched in aerobic respiration pathways and fatty acid and amino acid degradation. These observations indicate discrete but important differences in the gut microbiome of colic horses.